A Current Analysis of Black Head Football Coaches and Offensive Coordinators at the NCAA DI-FBS Level - Turick, Robert; Bopp, Trevor (Journal of Intercollegiate Sport, 2016)
At the start of the 2015 college football season, 15 of the 128 NCAA DI-FBS programs took the field with a new head coach. Of note, is that none of the newly hired head coaches were Black, and 11 of the 15 hires climbed the coaching ranks on the offensive side of the ball. Given that 11.7% of the head coaching jobs in the league were available this offseason and none were filled by a Black coaching candidate could signify that the positive trends found after the 2010 season regarding the hiring of Black head football coaches (Bopp & Sagas, 2012) may have plateaued, or even worse, declined. The purpose of this study was to ascertain if significant strides are being made in the promotion of Black coaches to head coach and offensive coordinator positions in college football, and evaluate how successful they have been in those positions. The findings of our study, which were interpreted using racial tasking (Bopp & Sagas, 2014) as our theoretical lens, found that a) Black representation at the head coach and offensive coordinator position has plateaued, b) White head coaches statistically have higher winning percentages than their Black counterparts, c) White head coaches are afforded nearly a year more on average than Black head coaches to lead their programs, and d) that White offensive coordinators tend to manage more prolific passing teams (e.g., attempts, yards, and touchdowns) than their Black counterparts. The performance of Black coaches compared with their White counterparts has not favored Black coaches which may create prejudice in the mind of athletic administrators. Implications and suggestions for change are discussed.